Rapid virus diagnosis application of immunofluorescence - Gardner, Phillip Samuel (Butterworths, 1980)
Rapid Virus Diagnosis: Application of Immunofluorescence presents developments in immunofluorescence as a technique for the diagnosis of virus infections. It discusses the effective and rapid methods for the diagnosis of virus infections. It addresses the application of fluorescent antibody techniques to the diagnosis and the investigation of virus infections and the assessment of their value both to the clinician and to the virologist